Factors associated with hemodialysis adequacy among end stage renal disease patients on maintenance hemodialysis in Rwanda - Ndahayo, Didace; Bimenyimana Gapira, Emmanuel; Mbabazi, Theos; Chironda, Geldine (International Journal of Advanced Nursing Studies, 2021)
The aim of this study was to assess the factors associated with dialysis adequacy in ESRD patients on maintenance hemodialysis in Rwanda. A descriptive cross-sectional study was conducted. A sample size of 66 hemodialysis patients was selected using purposive sampling strategy. An interview scheduled guide was used to collect data. Dialysis adequacy was calculated using kt/v Daugirdas & Schneditz formula. The mean hemodialysis adequacy was 1.26Â± 0.34. Most participants [41(62%)] had optimal hemodialysis adequacy of equal or greater than to 1.2, 19 (29%) had near optimal hemodialysis adequacy (0.8 - 1.2 kt/v) and only 6 (9%) had less than optimal hemodialysis adequacy (kt/v <0.8). Factors associated with hemodialysis adequacy were hospital settings (p = .010), age (p = .007), BMI (p =.004) and blood pressure level ((p = .018). Moreover, mode of transport and type of drinking water was significantly associated with hemodialysis adequacy (p = 0.032 and 0.030 respectively). In conclusion, the level of hemodialysis adequacy was low in 38% of ESRD patients with associated factors predominantly demographics. Therefore, further research inquiry is needed on additional factors which include technical aspects to establish their association with hemodialysis adequacy.Â Â